Decommissioning of coal-based plants in India and its ramifications - Somit Dasgupta (Indian Council for Research on International Economic Relations (ICRIER), 2024)
According to the International Energy Agency (IEA), the Indian power sector is the highest emitter of carbon dioxide (CO2). In 2021, the power sector emitted 1104 MT of CO2 which was about 45% of the total emissions. Next was the industrial sector which emitted about 762 MT of CO2. Within the industrial sector, the largest contribution was from the iron and steel industry estimated at 304 MT. India has declared its intention to become net-zero by 2070, and going by available literature, there is usually a 30-year gap between reaching peak emission levels and achieving net-zero. Going by this argument, India will probably have to peak its emissions by around 2040. The power sector being the largest emitter of CO2 has a key role to play if India wants to achieve its target of going net-zero by 2070. This will mean that we would need to move away from coal-based generation and adopt renewable power instead, mainly wind and solar. Of course, it can be supplemented with hydro power, biomass and nuclear. This energy transition can only happen if one is able to decommission coal-based plants without any adverse effect of not being able to meet the system demand. Countries like USA, UK and Germany have been able to move away from coal. They were able to do this primarily due to availability of gas and also through a system of giving market signals coupled with strict environmental norms for coal-based generation. The movement away from coal-based generation is not really working in the case of India for various reasons. India's proportion of coal-based generation has gone up in 2020 as compared to what it was in 2000. This is just the opposite of what has happened in USA, UK and Germany. In UK, coal-based generation today is only about 1.6% of total generation. India, unfortunately, does not have access to cheap gas and it has various other issues which are affecting the growth of hydro and nuclear power. Though India has ramped up its wind and solar generation manifold, it is still far behind if one is dreaming of replacing coal with renewable generation. This working paper examines as to what is the ideal parameter for decommissioning of coal-based generation. Is it the age of the plant, its station heat rate (SHR) or any other parameter? It also examines whether it would be possible for India to undertake this energy transition easily so as to become net-zero by 2070.
Keywords: Q40; Q48; 330; Coal; Decommissioning; Renewable